An Analysis of Gender Inequality Towards The Main Character Reflected In Marie Benedict's The Other Einstein Novel - Sarah Purnawati Siregar (Pendidikan Sejarah, 2023)
This research aims to analyze gender inequality that can be found in the novel of “The Other Einstein” by Marie Benedict. It focuses to analyze on the female main character, Mileva Maric, and the first wife of the infamous scientist, Albert Einstein. This research is descriptive qualitative research, using the method of library research to collect data and the method of descriptive analysis by Ratna. The theory uses to analyze the gender inequality acquired by Mileva is Longwe’s framework of women empowerment, structures into five levels of equality. It means that if all of the five levels are unable to be reached, empowerment is unable to fully be acquired by women. The research’s result showed that Mileva was unable to acquire the equality and full empowerment of women in the novel as the equality Mileva had received throughout the novel had only reached the lowest second level, access. While the rest higher three levels, conscientisation, participation, and control were not reached, and those equalities were not received by Mileva. It can be concluded that through this research, the equality level that had been reached by women in the culture and the times when Mileva lived around the end of 1890s and beginning of 1900s is on the level of access, the half of the women’s empowerment.